Slut-Shaming Towards Female Revenge Porn Victims: Analysis through Newsmaking Criminology and the Online Media Construction of Reality - Wahab, Amirah Hi; Hakim, Fany N. R. (Journal of Public Representative and Society Provision, 2025)
The prevalence of gender-based violence against women (GBVAW), including revenge porn as a form of technology-facilitated gender-based violence (TFGBV), reflects the evolving nature of crime alongside technological advances. The media plays an important role in shaping and disseminating information about crime, given that crime events do not directly affect every individual. Moreover, the media acts as a central agent in constructing the public’s perception of crime realities. Nonetheless, crime news frequently contains distortion and bias, resulting in a disparity between the actual social reality and how it is presented. This study explores the online mass media contribution to shaping public narratives regarding revenge porn cases involving female victims, with particular attention to the phenomenon of slut-shaming resulting from unbalanced reporting. The research employs a qualitative approach with content analysis, using the framework of newsmaking criminology. Two key indicators guide the analysis: media distortion in narrative construction and the sensationalization of crime news, as observed in six online media outlets operating through TikTok platform. The findings reveal that online media content disseminated via TikTok fosters public sexist reactions towards female revenge porn victims, often through slut-shaming practices. Media distortions and sensationalism contribute to a false perception associating revenge porn with pornography. As a result, victims are frequently labeled as “actors,” “players,” or even “porn stars,” despite their victimhood and the legal violations associated with such publications under Indonesian law.